THE ANALYSIS OF THE INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY ON COSTUMER LOYALTY ICE CREAM WALL’S - Juaniva Sidharta; Naibaho, Joshua Perkasa; Sinaga, Sautman (Universitas Kristen Indonesia, 2020)
Currently, business competition in the industry is getting tougher, one industry that has tough competition is the food & beverage industry. If competition in the industry increases, it will be difficult to find new consumers, while the company certainly wants a stable profit. Thus, the old company will try to maintain existing customer loyalty. In this study, we will examine, how brand image and product quality will be a weapon or asset for old company in business competition, and will also affect customer loyalty (in this case WALL’S). In this research will be conducted by descriptive analysis. The sample taken is people, who live in Limus Pratama Regency, as many as 100 respondents. And the variables used in this study are brand image, product quality, and costumer loyality. Keywords: brand image, product quality, costumer loyality.